2019
DOI: 10.1016/j.jdeveco.2018.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Do children benefit from internet access? Experimental evidence from Peru

Abstract: Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purpose other than for attribution, and the use of IDB's logo shall be subject to a separate written license agreement between the IDB and the user and is not authorized as part of this CC-IGO license. Following a peer review process, and with previous written consent by the Inter-American Development Bank (IDB), a revised ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 19 publications
3
18
0
5
Order By: Relevance
“…This requires regulation by internet providers in addition to supervision by guardians or adults. The results are consistent with previous studies (Malamud et al 2019;Cristia, Czerwonko, and Garofalo 2010;Malamud and Pop-Eleches 2011;Meza-Cordero 2017;Bet, Cristia, and Ibarrarán 2014) showing that increase in access to ICT increases digital skills.…”
Section: Quasi-experimental Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…This requires regulation by internet providers in addition to supervision by guardians or adults. The results are consistent with previous studies (Malamud et al 2019;Cristia, Czerwonko, and Garofalo 2010;Malamud and Pop-Eleches 2011;Meza-Cordero 2017;Bet, Cristia, and Ibarrarán 2014) showing that increase in access to ICT increases digital skills.…”
Section: Quasi-experimental Resultssupporting
confidence: 93%
“…Internet does improve satisfaction among students on the current use of ICT in schools (Panel D, Column 1). These results are in tandem with previous studies (Schofield and Davidson 2003;Malamud et al 2019) that internet use generates both direct and indirect effects in the United States (US) and Peru. For instance, Schofield and Davidson (2003)'s study found that internet use in schools increased student autonomy and relationship with their teachers.…”
Section: Effects On General Ict-related Skills and Knowledgesupporting
confidence: 89%
See 2 more Smart Citations
“…(2007) unlike other studies has found that there are no significant differences between men and women on the mean amount of time accessing the Internet every day. Malamud, et. al.…”
Section: Theoretical Implicationsmentioning
confidence: 99%